ChemInform Abstract: Three Dimensional Macroporous Architectures and Aerogels Built of Carbon Nanotubes and/or Graphene: Synthesis and Applications. Issue 21 (2nd May 2013) - Nardecchia, Stefania; Carriazo, Daniel; Ferrer, M. Luisa; Gutierrez, Maria C.; del Monte, Francisco
Abstract Review: 211 refs.